2000
DOI: 10.1016/s0014-5793(00)02002-0
|View full text |Cite
|
Sign up to set email alerts
|

Activation of signal transduction pathways involving trkA, PLCγ‐1, PKC isoforms and ERK‐1/2 by tetanus toxin

Abstract: Previous reports have demonstrated that tetanus toxin (TeTx) induces activation and down-regulation of protein kinase C (PKC). In the present work the differential activation of PKC isoforms and of signal transduction pathways, including nerve growth factor receptor trkA, phospholipase CQ Q-1 (PLCQ Q-1), and extracellular regulated kinases 1 and 2 (ERK-1/2) by TeTx in a synaptosome-enriched P 2 fraction from rat brain is reported. TeTx induces clear translocation from the soluble (cytosolic) compartment to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
23
0
3

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(32 citation statements)
references
References 39 publications
6
23
0
3
Order By: Relevance
“…The treatment of synaptosomes with 100 nM PMA (results not shown) induced a typical response in PKC isoforms, as described previously [25], proving the reliability of the system. The incubation of synaptosomes with increasing concentrations of H C -TeTx for 15 min induced changes in the distribution of PKC isoforms (Figure 1).…”
Section: Results H C -Tetx Induces Differential Translocation Of Pkc supporting
confidence: 81%
See 3 more Smart Citations
“…The treatment of synaptosomes with 100 nM PMA (results not shown) induced a typical response in PKC isoforms, as described previously [25], proving the reliability of the system. The incubation of synaptosomes with increasing concentrations of H C -TeTx for 15 min induced changes in the distribution of PKC isoforms (Figure 1).…”
Section: Results H C -Tetx Induces Differential Translocation Of Pkc supporting
confidence: 81%
“…The differential translocation of synaptosomal PKC isoforms in response to TeTx, as well as the induction of phosphorylation of trkA, PLCγ-1 and ERK-1\2 and activation of PKC isoforms, has recently been demonstrated by our group [25]. As a consequence of the results presented in the present work, we can attribute this signal activation to the H C -TeTx fragment.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…Our experiments indicate that the fused protein BDNF-TTC is functional in early apoptosis inhibition processes of the Neuro2A cell line as described for BDNF [40,41]. The present study, as well as previous work has shown that TTC can activate survival pathways in cells [34,35,42,43]. We report here that TTC also displays an antiapoptotic effect compared to control, although this effect was lower than the ones resulting from the treatment with the other two recombinant proteins ( Figure 3B) and also given that the TTC effect was lower than the others, we consider that the activity of the neurotrophic factor was maintained in our study.…”
Section: Discussionsupporting
confidence: 79%